PROBABILITY OF C02 PIPELINE USING FAULT TREE ANALYSIS AND FUZZY LOGIC - ALI BAIG, AHMED (2014)
Global warming is one ofthe key issues on which research and studies are being conducted all over the globe. Various methods of CO2 capture, reduction and reuse are being developed. Transportations of high concentration CO2 in process industries is carried out using pipelines. Initially the failure rates of natural gas pipeline were used for the risk estimations of CO2 pipelines. However with the laps of time, high uncertainty in the results urged the need of exploring this knowledge gap. This study emphasizes on estimating the reliable failure rate of a CO2 transporting pipeline. The purpose of this study is for the application in Carbon Capture and Storage (CCS) project. This research presents a methodology that uses Fault Tree Analysis (FTA) for analyzing the failure scenarios of possible incidents or accident that may occur in a CO2 pipeline. As for new systems such as CCS, the reliability and failure rate data is very limited. A Fuzzy Logic system is introduced to the method that uses the expert's qualitative judgment and converts it into quantified crisp value.